IMPACT OF OPERATION THEATRE EQUIPMENT EFFICIENCY AND ADMINISTRATION OF DRUGS WITH IV FLUIDS ON INTRA-OPERATIVE STABILITY AND POST-OPERATIVE PATIENT OUTCOMES (Journal of Medical & Health Sciences Review, 2025)
Background: The operation theatre (OT) is a specialized, sterile environment equipped with essential instruments and devices required for surgical procedures, including monitors, anesthesia machines, suction devices, and infusion pumps. Efficient functioning of these instruments, along with careful administration of drugs and IV fluids, is critical for maintaining intraoperative stability, ensuring patient safety, and minimizing postoperative complications.Introduction: Maintaining stable physiological parameters during surgery is essential for patient safety and optimal recovery. Factors such as the efficiency of the operation theatre, proper functioning of surgical instruments and equipment, and precise administration of drugs with IV fluids directly influence intraoperative stability and postoperative outcomes. Effective OT management ensures smooth surgical procedures, reduces the risk of complications, and contributes to faster and safer patient recovery.Objective: This study aims to investigate how the efficiency of operating theatre equipment and the correct use of drugs and intravenous fluids during surgery affect patient stability during the operation and their recovery after surgery.Methods: A descriptive observational study was carried out on 50 surgical patients. Before surgery, demographic details and vital signs were noted. During surgery, factors such as the condition of OT equipment, administration of IV fluids, drug-related issues, and episodes of low blood pressure were monitored. After surgery, any complications were recorded. Correlation analysis, descriptive statistics was then used to find the relationships between intraoperative factors and postoperative outcomes.Results: Most patients maintained stable intraoperative vital signs. Ringer’s Lactate was the predominant IV fluid administered. Intraoperative complications were rare, with hypotension and drug-related events occurring in only 1 patient each. Postoperative complications were minimal, affecting only 2 patients. Correlation analysis showed a significant relationship between intraoperative factors and postoperative outcomes.Conclusion: The study shows that well-functioning OT equipment, careful monitoring during surgery, and correct administration of IV fluids and drugs help keep patients stable during the operation and reduce complications afterward. Improving these practices supports safer surgeries and better recovery for patients.